2022
DOI: 10.3389/fped.2022.920066
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pediatric Asthma Therapy: Mepolizumab

Abstract: There is a growing need for advanced treatment in children with persistent and severe asthma symptoms. As a matter of fact, between 2 and 5% of asthmatic children experience repeated hospitalizations and poor quality of life despite optimized treatment with inhaled glucocorticoid plus a second controller. In this scenario, mepolizumab, a humanized monoclonal antibody, has proven to be effective in controlling eosinophil proliferation by targeting interleukin-5 (IL-5), a key mediator of eosinophil activation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Many studies prove the efficacy (reduction of exacerbation rate and hospital admission, steroids sparing effect) and safety (lower risk of severe adverse events) of anti-IL5 therapy in patients with severe asthma. 17 Like suggested by 2020 ERS/ATS, the CTS position statement advises against the use of anti-IL5 in pediatrics patients and suggests them as add on treatment in adults with eosinophilic severe uncontrolled asthma (SUA) and those with steroids dependency. 16 While the ERS/ATS Task Force does not suggest the use of anti-IL5 in children and adolescents due to the limited number of treated patients in this age group, 13 the ALAT guideline recommends the prescription of anti-IL5 antibodies (mepolizumab and reslizumab) in patients aged >12 years because the studies included in the analysis reported the reduction of asthma exacerbations rate and the lowering of blood and sputum eosinophils count.…”
Section: Anti-il5 Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies prove the efficacy (reduction of exacerbation rate and hospital admission, steroids sparing effect) and safety (lower risk of severe adverse events) of anti-IL5 therapy in patients with severe asthma. 17 Like suggested by 2020 ERS/ATS, the CTS position statement advises against the use of anti-IL5 in pediatrics patients and suggests them as add on treatment in adults with eosinophilic severe uncontrolled asthma (SUA) and those with steroids dependency. 16 While the ERS/ATS Task Force does not suggest the use of anti-IL5 in children and adolescents due to the limited number of treated patients in this age group, 13 the ALAT guideline recommends the prescription of anti-IL5 antibodies (mepolizumab and reslizumab) in patients aged >12 years because the studies included in the analysis reported the reduction of asthma exacerbations rate and the lowering of blood and sputum eosinophils count.…”
Section: Anti-il5 Antibodiesmentioning
confidence: 99%
“…Many studies prove the efficacy (reduction of exacerbation rate and hospital admission, steroids sparing effect) and safety (lower risk of severe adverse events) of anti‐IL5 therapy in patients with severe asthma 17 …”
Section: Compared Documents On Severe Asthma Managementmentioning
confidence: 99%
“…Ullmann et al 11 The authors found that dupilumab was associated with higher costs per patient over a 6 year period ($379 USD per patient per exacerbation for dupilumab compared to $19 USD per patient for standard treatment). 12 These results were similar to other economic analyses performed on adolescents and adults with asthma in Colombia.…”
Section: Updates In Biologic Treatments and Alternative Interventions...mentioning
confidence: 99%
“…The antibody exhibited a beneficial effect on type 2 inflammatory markers, decreasing allergic inflammation markers in all CF patients ( Zhang et al, 2020 ). Recently, the outcome of clinical trials showed that mepolizumab is a safe and focused step-up therapy for children and adolescents with severe asthma with an eosinophilic phenotype ( Ullmann et al, 2022 ).…”
Section: Monoclonal Antibodies Are Target-specificmentioning
confidence: 99%